Penggunaan Kosmetik Berbahaya dalam Persfektif Hukum Islam - Lesnida, Lesnida (STAI Serdang Lubuk Pakam, 2021)
The rampant circulation of dangerous cosmetics is something that needs to be watched out for, because in addition to violating the law, its existence can also endanger its users. Cosmetics that basically function as self-decoration turn into self-destructors. On that basis, this study aims to analyze the law on the use of harmful cosmetics in the perspective of Islamic law. This study uses a qualitative research method based on library research. The main data sources are the Qur'an and Hadith, and the supporting data sources are the thoughts of the four imams of the schools (Hanafi, Maliki, Shafi'i, and Hambali) and fatwa the Indonesian Ulama Council. The results of the study indicate that the use of harmful cosmetics is forbidden in Islam, this is in accordance with the word of Allah in the Qur'an Surah al-Ahzab verse 33. All the Imams of the Schools state that the factors of the prohibition of cosmetics are seen from three things, namely the ingredients of manufacture, the method of making them, and the impact it has. If one of the three things is haram, then the cosmetic is not allowed to be used. In addition, in terms of use, Muslims should use cosmetics that have been registered with the Food and Drug Inspection Agency, and also have a halal label issued by the Indonesian Ulama Council.